Design optimization of cutting parameters for truning operation based on Taguchi method - Muhammad Al Firdausi, Johari (2008)
Modern manufacturers, seeking to remain competitive in the market, rely on their manufacturing engineers and production personnel to quickly and effectively set up manufacturing processes for new products. Taguchi Parameter Design is a powerful and efficient method for optimizing quality and performance output of manufacturing processes, thus a powerful tool for meeting this challenge. This thesis discusses an investigation into the use of Taguchi Parameter Design for optimizing surface roughness generated by a conventional lathe. Control parameters being consider in this thesis are spindle speed, feed rate and depth of cut. After experimentally turning sample workpieces using the selected orthogonal array and parameters, this study expected to produce an optimum combination of controlled parameter for the surface roughness.